Wireless networking for moving objects : protocols, architectures, tools, services and applications - Curado, Marília; Kassler, Andreas; Ganchev, Ivan (Lecture Notes in Computer Science, 2014)
Wireless networks of moving objects have drawn significant attention recently. These types of networks consist of a number of autonomous or semi-autonomous wireless nodes/objects moving with diverse patterns and speeds while communicating via several radio interfaces simultaneously. To overcome current shortcomings, a number of research challenges have to be addressed in this area, ranging from initial conceptualization and modelling, to protocols and architectures engineering, and development of suitable tools, applications and services, and to the elaboration of realistic use-case scenarios by taking into account corresponding societal and economic aspects. By applying a systematic approach the objective of this book is to assess the state of the art and consolidate the main research results achieved in this area. It was prepared as the Final Publication of the COST Action IC0906 "Wireless Networking for Moving Objects (WiNeMO)". The book contains 15 chapters and is a show-case of the main outcomes of the action in line with its scientific goals. The book will serve as a valuable reference for undergraduate students, post-graduate students, educators, faculty members, researchers, engineers, and research strategists working in this field.